2022
DOI: 10.1186/s12889-022-13347-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with ownership and utilization of insecticide treated nets among children under five years in sub-Saharan Africa

Abstract: Background Insecticide-treated net (ITN) is a cost-effective means to control malaria and morbidity in under-five children. This study synthesizes the factors associated with using the ITN as a malaria prevention tool in sub-Saharan Africa. Methods There was an advanced search of four electronic databases, including PubMed Central, CINAHL, EMBASE, and Google Scholar, and identified articles between 2016 to April 2021. Following the title, abstract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The low availability and ownership of ITNs signi cantly in uence ITN use since strategies for ITN access and ownership are mainly geared towards mass distributions of ITNs rather than towards targeted distributions based on intrahousehold (rooms available for sleeping, household size and composition, household relationship structure including other factors). Indeed, the targeted distribution of ITNs has been shown to effectively increase ITN use, especially among children under ve years of age [23,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low availability and ownership of ITNs signi cantly in uence ITN use since strategies for ITN access and ownership are mainly geared towards mass distributions of ITNs rather than towards targeted distributions based on intrahousehold (rooms available for sleeping, household size and composition, household relationship structure including other factors). Indeed, the targeted distribution of ITNs has been shown to effectively increase ITN use, especially among children under ve years of age [23,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…This might lead to errors in the measurement of ITN use caused by social desirability bias, where households will probably overreport the number of household members sleeping under ITNs in the survey. Finally, the analysis of ITN use and its determinants based on the theoretical model is not widely extensive, as it excludes interactions at broader levels (employment, education, social and community networks, and the general socioeconomic, cultural, and environmental conditions), which have been explored in other studies [12,13,16,22,23].…”
Section: Limitationsmentioning
confidence: 99%
“…Low availability and ownership of ITNs signi cantly in uence ITN use since strategies for ITN access and ownership are mainly geared towards mass distributions of ITNs rather than on targeted distribution based on intra-household factors (rooms available for sleeping, household size and composition, household relationship structure including other factors). Indeed, targeted distribution of ITNs has been shown to effectively increase ITN use especially among children under ve years [23,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…It intends to provide an indepth understanding of context-speci c factors associated with ITN use to address the gap in ITN ownership and use at the household level. Much as several studies have analyzed the gap between ITN access, ITN ownership, and ITN use [16,20,22,23]; these studies have often examined a general relationship among factors at various levels and not speci cally the interaction among speci c factors such as children under ve years on household´s ownership and household members ITN use.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a previous study indicated ITN use in rural areas of Rwanda to be 57% [18], a utilization rate that is extremely lower compared to the targeted 85% set by the Rwanda National malaria control program and previously recorded rates [15,18]. Other factors previously associated with the utilization of bed nets include number of household members, with lower use among households with ve or more members; number of bed nets present in households, with high numbers positively correlating with greater usage; employment status, maternal educational attainment and ANC attendance and awareness of the importance bed net use [17,19,20].…”
Section: Introductionmentioning
confidence: 94%